Unreasonable men : masculinity and social theory - Seidler, Victor J., 1945- (Male orders, 2013)
This much needed book is the first to show how dominant forms of masculinity are implicated in the traditions of social theory that have emerged since the Enlightenment. The author shows how an 'unreasonable' form of reason has emerged from the separation of reason from emotion, mind from body, nature from culture, public from private, matter from spirit - the dualities that have shaped our vision of modernity. The book argues that men need to explore critically their power and experience which has been rendered invisible by the dominant traditions of social theory. Instead of legislating for others they have to learn to speak more personally for themselves.